A novel dynamometer for the standardisation of the force applied during distal forelimb flexion tests in horses. (26th July 2020) - Nocera, I.; Sgorbini, M.; Gracia‐Calvo, L. A.; Cacini, M.; Vitale, V.; Citi, S.
Summary: Variability in the technique employed for flexion tests may produce different responses and veterinary assessments. We propose a novel custom‐designed dynamometer and compare the results with the literature. Ten horses were enrolled in the present study, with a total of 20 forelimbs. The horses were found to be healthy based on orthopaedic and radiographic examination of the distal forelimb region, performed on both limbs. Lower forelimb flexion tests were performed by applying three different forces (75, 100 and 120 N), measured with a dynamometer, for one minute, with a time interval of 48 h between each test. Each horse was trotted before and after the flexion test. The experiment was videotaped, and the responses were assessed randomly and blindly by three experienced equine veterinarians. None of the horses responded with a lameness grade exceeding 1/5 on a numerical 6‐point scale. Two out of three veterinarians detected a increased degree of lameness between the minimum and the maximum force applied, while one veterinarian showed no change in the interpretation of the flexion test for all three applied forces. A mild agreement was detected between veterinarian A and B, applying a force of 100 N, and between A and C, with 120 N; a moderate agreement was found between veterinarian A and B, with 120 N. The chi‐square test showed that the results observed were only like the expected ones for 100 N. With a force of 100 N, there is no relationship between intensity and the evaluation of lameness; consequently, 100 N could be used to achieve a real standardisation of the lameness score. The use of the dynamometer was found to be easy and practical. It also enabled the applied force and the manipulation technique to be objectified.